2008
DOI: 10.1093/pubmed/fdn045
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of screening high-risk groups for anal cancer

Abstract: There are major areas of uncertainty. New analyses of existing primary data, undertaken specifically to inform regression rates may usefully update key parameters at little additional cost. If these analyses increase the likelihood that screening is cost-effective, further studies of the utility effects of treatment for high-grade AIN, and potential screening attendance rates may be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…In 2007, the New York State Department of Health AIDS Institute issued guidelines supporting cytology screening at baseline and annually in HIV-infected MSM, persons with a history of anogenital condyloma, and HIV-infected women with a history of lower tract genital disease. Annual cytology screening in HIV-infected MSM and biannually in HIV-uninfected MSM was shown to be cost effective in two studies using Markov modeling in the United States, but annual screening of MSM was not found to be cost effective in a United Kingdom study (Goldie, Kuntz, Weinstein, Freedberg, & Palefsky, 2000;Goldie et al, 1999;Karnon, Jones, Czoski-Murray, & Smith, 2008).…”
Section: Frequency Of Screeningmentioning
confidence: 97%
“…In 2007, the New York State Department of Health AIDS Institute issued guidelines supporting cytology screening at baseline and annually in HIV-infected MSM, persons with a history of anogenital condyloma, and HIV-infected women with a history of lower tract genital disease. Annual cytology screening in HIV-infected MSM and biannually in HIV-uninfected MSM was shown to be cost effective in two studies using Markov modeling in the United States, but annual screening of MSM was not found to be cost effective in a United Kingdom study (Goldie, Kuntz, Weinstein, Freedberg, & Palefsky, 2000;Goldie et al, 1999;Karnon, Jones, Czoski-Murray, & Smith, 2008).…”
Section: Frequency Of Screeningmentioning
confidence: 97%
“…In addition to these, the model included health states for HIV progression based on the patient’s CD4 count (i.e., CD4 >500 cells/mm 3 , CD4 between 200–500 cells/mm 3 , and CD4 <200 cells/mm 3 ). Patient CD4 count, rates of HSIL progression or regression, and natural history post initial regression were obtained from the literature or calibrated using a separate natural history model for anal carcinogenesis (Appendix S1.3; Appendix Table T1.1 and T1.2) [2, 9, 19, 29–31]. Our model also considered the possibility of receiving antiretroviral therapy (ART) and the impact of change in CD4 count on anal carcinogenesis.…”
Section: Methodsmentioning
confidence: 99%
“…Cost data were estimated using the Surveillance, Epidemiology, and End Results (SEER) database and Medicare claims (Appendix Table T1.4) as well as obtained from published studies [28, 29, 33]. Health-state utilities (preference-based valuation of quality of life) were identified from the literature (Appendix Table T1.4) [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-risk groups considered candidates for screening include both HIV-positive and HIV-negative men who have sex with men (MSM) [2,3] and women who are HIV-positive [4,5]. Although some modeling studies have concluded that anal cytology screening is likely to be cost-effective [6,7,8], groups such as the United States Preventive Services Task Force, the American Cancer Society, the Centers for Disease Control and the Infectious Diseases Society of America do not support routine anal cytology screening [9]. There are no national screening guidelines for anal cancer, and investigators have suggested different abnormal anal cytologic result thresholds for referral of patients with abnormal anal cytology to high-resolution anoscopy (HRA) and directed biopsy [3,10,11].…”
Section: Introductionmentioning
confidence: 99%